The impact of government debt on output growth, private investment and human capital in Malaysia - Hajian, Hoda; Kaliappan, Shivee Ranjanee (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
It is important for every country to evaluate the role of government debt on economic growth and macroeconomic factors, especially in developing economies. Some endogenous growth theories predict that if government debt at moderate level is spent on development expenditures such as public infrastructure and human capital – as is the case in Malaysia – it can crowd-in private investment, human capital and economic growth. This paper aims to examine the effect of government debt on output growth, private investment and human capital in Malaysia during the period of 1985-2016, employing Vector Error Correction modeling (VECM) and Generalized Impulse Response (GIR). The result shows that government debt generates positive response in GDP growth and human capital in the long run although not significant. Moreover, the effect on private investment is null. This finding supports prudent debt management in Malaysia. Accordingly, the policy implication would be to focus on more efficient usage and allocation of the government funds, based on the country’s priorities, while maintaining the debt within the dominant past range.